Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve the given system of equations for [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
[tex]\[ 3^{2y + x} = 3^5 \][/tex]
[tex]\[ y = 2x(x - 3) - 8 \][/tex]
Let's proceed step by step:
### Step 1: Solve the first equation
We have the equation:
[tex]\[ 3^{2y + x} = 3^5 \][/tex]
Since the bases are the same, we can equate the exponents:
[tex]\[ 2y + x = 5 \][/tex]
This simplifies to:
[tex]\[ 2y = 5 - x \][/tex]
[tex]\[ y = \frac{5 - x}{2} \][/tex]
### Step 2: Substitute [tex]\( y \)[/tex] in the second equation
We now substitute [tex]\( y = \frac{5 - x}{2} \)[/tex] into the second equation:
[tex]\[ y = 2x(x - 3) - 8 \][/tex]
Substituting [tex]\( y \)[/tex]:
[tex]\[ \frac{5 - x}{2} = 2x(x - 3) - 8 \][/tex]
### Step 3: Simplify and solve for [tex]\( x \)[/tex]
First, clear the fraction by multiplying both sides by 2:
[tex]\[ 5 - x = 4x(x - 3) - 16 \][/tex]
Simplify the right side:
[tex]\[ 5 - x = 4x^2 - 12x - 16 \][/tex]
Rearrange all terms to one side to form a quadratic equation:
[tex]\[ 4x^2 - 12x - 16 + x - 5 = 0 \][/tex]
[tex]\[ 4x^2 - 11x - 21 = 0 \][/tex]
### Step 4: Solve the quadratic equation
To solve [tex]\( 4x^2 - 11x - 21 = 0 \)[/tex], we use the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\( a = 4 \)[/tex], [tex]\( b = -11 \)[/tex], and [tex]\( c = -21 \)[/tex].
Calculate the discriminant:
[tex]\[ b^2 - 4ac = (-11)^2 - 4(4)(-21) = 121 + 336 = 457 \][/tex]
Thus:
[tex]\[ x = \frac{11 \pm \sqrt{457}}{8} \][/tex]
### Step 5: Calculate the values
The solutions for [tex]\( x \)[/tex] are:
[tex]\[ x_1 = \frac{11 + \sqrt{457}}{8} \][/tex]
[tex]\[ x_2 = \frac{11 - \sqrt{457}}{8} \][/tex]
### Step 6: Find corresponding [tex]\( y \)[/tex] values
Using [tex]\( y = \frac{5 - x}{2} \)[/tex], we find [tex]\( y \)[/tex] for each [tex]\( x \)[/tex]:
For [tex]\( x_1 = \frac{11 + \sqrt{457}}{8} \)[/tex]:
[tex]\[ y_1 = \frac{5 - \frac{11 + \sqrt{457}}{8}}{2} = \frac{40 - 11 - \sqrt{457}}{16} = \frac{29 - \sqrt{457}}{16} \][/tex]
For [tex]\( x_2 = \frac{11 - \sqrt{457}}{8} \)[/tex]:
[tex]\[ y_2 = \frac{5 - \frac{11 - \sqrt{457}}{8}}{2} = \frac{40 - 11 + \sqrt{457}}{16} = \frac{29 + \sqrt{457}}{16} \][/tex]
### Final Solution
Therefore, the solutions for [tex]\( (x, y) \)[/tex] are:
[tex]\[ \left( \frac{11 + \sqrt{457}}{8}, \frac{29 - \sqrt{457}}{16} \right) \][/tex]
and
[tex]\[ \left( \frac{11 - \sqrt{457}}{8}, \frac{29 + \sqrt{457}}{16} \right) \][/tex]
[tex]\[ 3^{2y + x} = 3^5 \][/tex]
[tex]\[ y = 2x(x - 3) - 8 \][/tex]
Let's proceed step by step:
### Step 1: Solve the first equation
We have the equation:
[tex]\[ 3^{2y + x} = 3^5 \][/tex]
Since the bases are the same, we can equate the exponents:
[tex]\[ 2y + x = 5 \][/tex]
This simplifies to:
[tex]\[ 2y = 5 - x \][/tex]
[tex]\[ y = \frac{5 - x}{2} \][/tex]
### Step 2: Substitute [tex]\( y \)[/tex] in the second equation
We now substitute [tex]\( y = \frac{5 - x}{2} \)[/tex] into the second equation:
[tex]\[ y = 2x(x - 3) - 8 \][/tex]
Substituting [tex]\( y \)[/tex]:
[tex]\[ \frac{5 - x}{2} = 2x(x - 3) - 8 \][/tex]
### Step 3: Simplify and solve for [tex]\( x \)[/tex]
First, clear the fraction by multiplying both sides by 2:
[tex]\[ 5 - x = 4x(x - 3) - 16 \][/tex]
Simplify the right side:
[tex]\[ 5 - x = 4x^2 - 12x - 16 \][/tex]
Rearrange all terms to one side to form a quadratic equation:
[tex]\[ 4x^2 - 12x - 16 + x - 5 = 0 \][/tex]
[tex]\[ 4x^2 - 11x - 21 = 0 \][/tex]
### Step 4: Solve the quadratic equation
To solve [tex]\( 4x^2 - 11x - 21 = 0 \)[/tex], we use the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\( a = 4 \)[/tex], [tex]\( b = -11 \)[/tex], and [tex]\( c = -21 \)[/tex].
Calculate the discriminant:
[tex]\[ b^2 - 4ac = (-11)^2 - 4(4)(-21) = 121 + 336 = 457 \][/tex]
Thus:
[tex]\[ x = \frac{11 \pm \sqrt{457}}{8} \][/tex]
### Step 5: Calculate the values
The solutions for [tex]\( x \)[/tex] are:
[tex]\[ x_1 = \frac{11 + \sqrt{457}}{8} \][/tex]
[tex]\[ x_2 = \frac{11 - \sqrt{457}}{8} \][/tex]
### Step 6: Find corresponding [tex]\( y \)[/tex] values
Using [tex]\( y = \frac{5 - x}{2} \)[/tex], we find [tex]\( y \)[/tex] for each [tex]\( x \)[/tex]:
For [tex]\( x_1 = \frac{11 + \sqrt{457}}{8} \)[/tex]:
[tex]\[ y_1 = \frac{5 - \frac{11 + \sqrt{457}}{8}}{2} = \frac{40 - 11 - \sqrt{457}}{16} = \frac{29 - \sqrt{457}}{16} \][/tex]
For [tex]\( x_2 = \frac{11 - \sqrt{457}}{8} \)[/tex]:
[tex]\[ y_2 = \frac{5 - \frac{11 - \sqrt{457}}{8}}{2} = \frac{40 - 11 + \sqrt{457}}{16} = \frac{29 + \sqrt{457}}{16} \][/tex]
### Final Solution
Therefore, the solutions for [tex]\( (x, y) \)[/tex] are:
[tex]\[ \left( \frac{11 + \sqrt{457}}{8}, \frac{29 - \sqrt{457}}{16} \right) \][/tex]
and
[tex]\[ \left( \frac{11 - \sqrt{457}}{8}, \frac{29 + \sqrt{457}}{16} \right) \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.